2018
DOI: 10.1016/j.jhydrol.2018.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of peak flow to the change of rainfall temporal pattern due to warmer climate

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/userguides/explore-bristol-research/ebr-terms/ Sensitivity of peak flow to the change of rainfall temporal pattern1 due to warmer climate 2 Abstract 8The widely used design storms in urban drainage networks has different drawbacks. One of 9 them is that the shape of the rainfall temporal pattern is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 26 publications
2
38
0
1
Order By: Relevance
“…With developed areas more likely to have positive flood trends (Vogel et al, ), further urbanization will result in increased flood magnitudes (Shuster et al, ; Villarini et al, ), and the sensitivity of urban flood increases to temperature is likely to be higher (closer to precipitation sensitivities) than for nonurban catchments. Storm intensification will further compound this increase as more rain falls in a shorter period of time, at least for small urban catchments (Fadhel et al, ; Hettiarachchi et al, ; Wasko & Sharma, ).…”
Section: Expected Changesmentioning
confidence: 99%
“…With developed areas more likely to have positive flood trends (Vogel et al, ), further urbanization will result in increased flood magnitudes (Shuster et al, ; Villarini et al, ), and the sensitivity of urban flood increases to temperature is likely to be higher (closer to precipitation sensitivities) than for nonurban catchments. Storm intensification will further compound this increase as more rain falls in a shorter period of time, at least for small urban catchments (Fadhel et al, ; Hettiarachchi et al, ; Wasko & Sharma, ).…”
Section: Expected Changesmentioning
confidence: 99%
“…Wasko and Sharma () and Fadhel et al . () found that at higher temperatures, the temporal rainfall patterns become less uniform with more intense rainfall during peak times and reduced rainfall during less intense times for hourly‐scale storms. Furthermore, Hettiarachchi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Farmers' perceptions of climate change are also relevant as they are related to their farming decisions and practice [60]. Statements related to these phenomena identified from the literature [61][62][63][64][65][66][67][68][69] were used to evaluate farmers' agreement or disagreement using a Likert-type scale ranging from one to nine, where one corresponds to absolute disagreement and nine corresponds to absolute agreement with the statement. The proposed statements allow an assessment of farmers' opinions on issues such as the instability of meteorological factors and events related to climatic conditions.…”
Section: Farmers' Perceptions Of Climate Changementioning
confidence: 99%